Breast conserving therapy versus mastectomy in young breast cancer patients in asian settings / Siamala Sinnadurai - Siamala, Sinnadurai (2018)
Several studies in Asia point towards high mastectomy rates among patients with early stage breast cancer. In the current study, we assessed the surgical trends in young Asian women with early breast cancer, and compared overall survival (OS) following breast conserving therapy (BCT) versus mastectomy in these patients. Patients aged <50 years diagnosed with stage I or stage II breast cancer between 1990 and 2012 in four hospitals in Malaysia, Singapore and Hong Kong were included (N=3536). Logistic regression analyses were performed to determine the demographic and clinical factors associated with type of surgery. Through a Cox regression analysis, mortality in patients subjected to BCT were compared to those receiving mastectomy, while adjusting for possible confounders using propensity score method. Most patients received mastectomy (63.5%). Over 15 years, rates of BCT increased substantially in Singapore, whereas only a modest increase was observed in Malaysia, and no change in trend was observed in Hong Kong. BCT was significantly associated with Malay ethnicity, smaller tumours, no lymph node involvement, low grade tumours, hormonal receptor positivity, lack of HER2 expression, and no adjuvant chemotherapy. Nevertheless, survival was not significantly different between women receiving BCT and mastectomy; 5-year OS; 94.9% (95%CI 93.5 to 96.3) and 92.9% (95%CI 91.7 to 94.1), respectively; the 10-year OS; 87.0% (95% CI, 84.5- 89.6) and 84.8% (95% CI, 84.6 – 85.0), respectively. The adjusted hazard ratio comparing BCT versus mastectomy was 0.82 (95%CI, 0.64-1.04),showing no significant differences in survival between the two surgical groups. Subgroup analyses by country and ethnicity did not change the main inference. Findings from this study will be useful in facilitating surgical decision-making in young Asian breast cancer patients. As there appears to be no significant survival difference between patients undergoing BCT and mastectomy, iv eligible young breast cancer patients in Asian settings should be counseled to opt for BCT, which is less disfiguring.